STRATEGI PUBLIC RELATIONS DALAM MENANGANI PEMBERITAAN NEGATIF DI MEDIA MASSA PADA PT LION MENTARI AIRLINES - Novi Dian Oktavia; Hery Sawiji; Tutik Susilowati (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2020)
This study aimed to find out: 1) Public Relations strategies in handling negative news in the mass media at PT Lion Mentari Airlines, 2) obstacles encountered by Public Relations at PT Lion Mentari Airlines in handling negative news in the mass media, and 3) efforts to deal with the obstacles faced by Public Relations at PT Lion Mentari Airlines in handling negative news in the mass media.The type of research used was qualitative with a single embedded case study approach. The sampling technique was purposive and snowball sampling. The data collection technique used interviews, observation, and document analysis. The data validity test used was the triangulation of sources and methods. The data analysis use interactive technique consisted of data reduction, data display, drawing conclusion and verification.The results showed that: 1) Public Relations strategies in handling negative news in the mass media at PT Lion Mentari Airlines were through several stages, including Public Relations strategies, evaluation, and impact; 2) obstacles experienced by Public Relations at PT Lion Mentari Airlines in handling negative news in the mass media were operational technical obstacles, hoax news spread by the media, and situational obstacles; and 3) efforts to overcome the obstacles faced by Public Relations at PT Lion Mentari Airlines in handling negative news in the mass media were providing compensation in accordance with the applicable SOP, providing clarification sustainably in the form of information and records relevant to actual events objectively as well as establishing good relations with media relations, and arranging coordination between one party and another.